Semaglutid - prvi peroralni agonist receptorjev GLP-1 za zdravljenje sladkorne bolezni tipa 2 - Jovanović, Marija (Farmacevtski vestnik, 2022)
Optimal glycemic control and multifactorial treatment are important for type 2 diabetes control. Non-pharmacological treatment is the mainstay of antihyperglycemic treatment, but it usually merits timely escalation of pharmacological intervention. One of the barriers to pharmacological treatment with GLP-1 receptor agonists was injectable treatment due to their polypeptide composition. In 2019, the first and only oral GLP-1 receptor agonist – semaglutide, was introduced to clinical use. Due to structural modifications and technological processing of the tablet, the molecule is resistant to degradation in the acidic gastric envi- ronment and has a comparable effect as in the form of injectable treatment. Oral semaglutide was effective in improving glycemic control and redu- cing body weight, and proven for its cardiovascular safety. The present article describes the mechanism of action of GLP-1 receptor agonists, the development of oral semaglutide, dosing instructions and data from studies of its efficacy and safety.
Keywords: agonisti receptorjev GLP-1; antidiabetično zdravljenje; antihyperglycaemic treatment; GLP-1 receptor agonists; oral semaglutide; peroralni semaglutid